Prognostic predictor at Pediatrics Intensive Care Unit (PICU) with Pediatric Risk of Mortality III (PRISM III) scores - Vita Susianawati; Purnomo Suryantoro; Roni Naning (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
Various mortality prognostic scoring system are available for predicting mortality risk in PediatricIntensive Care Unit (PICU). The Pediatric Risk of Mortality III (PRISM III) scoring system is one ofthe main indicators used in the PICU. This study was conducted to evaluate the PRISM III asprognostic predictor in PICU. This was a cohort study involving 64 patients who admitted toPICU in Dr. Sardjito General Hospital, Yogyakarta and met inclusion and exclusion criteria. Theclinical state of patients were assessed and the PRISM III scores corresponding to the firs 24hours of hospitalization were calculated. Outcome analysis was defined either as death ordischarged from the hospital were recorded.Multivariateanalysiswas performed to find outindependent predictive factor that influence the outcome of death.The discriminative power ofthe model was calculated based on the receiver operator curve (ROC). The result showed thatmental status (relative risk/RR: 13.21; 95%CI: 1.18-14.80), White Blood Count/WBC (RR: 19.51;95%CI: 18.12-25.15) and Blood Urea Nitrogen/BUN (RR:22.87; 95%CI:1.85-28.20) were foundto be the main predictive factors of death in PICU. The cut off value of 51 of PRISM III scoreyielded the best sensitivity (83%) and specificity (69%). In conclusion,PRISM III score can beused as a prognostic predictor to determine the death risk ofpatients hospitalized at PICU.